Makna Leksikal dan Gramatikal dalam Bahasa Iklan Dompet Digital di Youtube: Kajian Semantik - Indah Sulmayanti; Ni Komang Ambarawati; Niah Rahmadani; Olivina Putri Noveni; Ratna Susanti (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2026)
The rapid growth of digital advertising has transformed the use of language into a strategic tool for conveying information and persuading consumers, particularly in digital wallet advertisements disseminated through YouTube. This study aims to describe the lexical and grammatical meanings embedded in the language of digital wallet advertisements on YouTube. A descriptive qualitative approach was employed using data comprising words, phrases, and sentences extracted from the official advertisements of DANA, GoPay, OVO, and ShopeePay uploaded between February and September 2025. Data were collected through digital observation and note-taking and analyzed using the interactive model of Miles and Huberman. The findings identified six instances of lexical meaning and eight instances of grammatical meaning. Lexical meanings retained their dictionary definitions independent of grammatical context, whereas grammatical meanings emerged through morphological processes, including prefixation, suffixation, circumfixation, and compounding. These linguistic patterns demonstrate that lexical meaning primarily facilitates clear and explicit product communication, while grammatical meaning reinforces persuasive intent, strengthens consumer trust, and enhances the communicative effectiveness of digital advertising discourse. This study extends semantic research by providing a comprehensive analysis of lexical and grammatical meanings across the complete discourse of digital wallet advertisements on YouTube.